Cross my heart and hope to spy - Carter, Ally. (New York : Hyperion, 2007)
Cammie Morgan is a CIA legacy and attends the premier school for spies in the world. The school hosts some mysterious guests with the code name Blackthorne. When Cammie is blamed for a security breach that threatens to expose the school's top secret status, she and her friends face danger to clear Cammie's name and learn the truth about Blackthorne.
Keywords: Spy stories; Spies -- Fiction; Spy stories; Dating (Social customs) -- Fiction; Private schools -- Fiction; School stories; Young adult fiction; Spy stories